2019
DOI: 10.1016/j.foodchem.2019.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Healthy novel gluten-free formulations based on beans, carob fruit and rice: Extrusion effect on organic acids, tocopherols, phenolic compounds and bioactivity

Abstract: Rice and legumes have great potential in the development of novel gluten-free snacks that are healthier than traditional snacks. Novel gluten-free extruded foods (composed of rice: 50-80%, beans: 20-40% and carob: 5-10%) were analysed and the extrusion effects regarding organic acids, tocopherols, phenolic compounds and bioactive properties were evaluated. The total concentration of organic acids was not significantly affected by extrusion, while tocopherols showed a significant reduction. Extrusion did not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
(45 reference statements)
2
32
0
Order By: Relevance
“…For instance, the Di-caff acid and Fer phenolic acid mixtures increased their amount during extrusion, reaching values of 57.22 µg/g d.w. and 40.22 µg/g d.w., starting from initial values of 47.06 µg/g d.w. and 31.37 µg/g d.w in mixtures, respectively. This is in line with Arribas et al [56] who showed that organic acids from rice and legumes were not significantly affected by the extrusion process and with Cruz et al [57] who reported an increase of phenolic acids during extrusion.…”
Section: Antioxidant Phenolic Acids Folates and Flavonoids Contentsupporting
confidence: 89%
“…For instance, the Di-caff acid and Fer phenolic acid mixtures increased their amount during extrusion, reaching values of 57.22 µg/g d.w. and 40.22 µg/g d.w., starting from initial values of 47.06 µg/g d.w. and 31.37 µg/g d.w in mixtures, respectively. This is in line with Arribas et al [56] who showed that organic acids from rice and legumes were not significantly affected by the extrusion process and with Cruz et al [57] who reported an increase of phenolic acids during extrusion.…”
Section: Antioxidant Phenolic Acids Folates and Flavonoids Contentsupporting
confidence: 89%
“…Extrusion allows for the development of novel food products with new physical and structural properties. However, most of the food technology processes, including extrusion, can results in changes of the content of nutritional and phenolic compounds (Arribas et al, ; Arribas, Cabellos, Cuadrado, Guillamón, & Pedrosa, ; Garcia‐Amezquita et al, ; Wang, Gu, & Ganjyal, ).…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion/cooking also affects the content of the bioactive compounds/anti-nutritional factors present in the raw materials. In the literature, there are studies that reported either their increase or their reduction, mainly depending on the raw material and the extrusion parameters; moreover, not all the bioactive compounds were affected to the same extent under the same extrusion conditions [13,18,37,65,93,[98][99][100][101][102][103][104]. As has been stated previously in this review, in many cases, the elimination of some phytochemicals is not desirable, since small amounts are able to produce beneficial health effects against different chronic diseases [3,9,21,105].…”
Section: Extrusion/cooking Processmentioning
confidence: 96%